Strain-induced crystallization behaviour of natural rubbers from guayule and rubber dandelion revealed by simultaneous time-resolved WAXD/tensile measurements: indispensable function for sustainable resources. Issue 98 (7th October 2016) - Ikeda, Yuko; Junkong, Preeyanuch; Ohashi, Takumi; Phakkeeree, Treethip; Sakaki, Yuta; Tohsan, Atitaya; Kohjiya, Shinzo; Cornish, Katrina
Abstract : Guayule and rubber dandelion natural rubbers are useful alternatives for Hevea natural rubber in terms of their strain-induced crystallization behaviours. Abstract : Because strain-induced crystallization (SIC) behaviour is the key for predicting the performance of alternatives to Hevea natural rubber, characteristics of the SIC of sulfur crosslinked guayule and dandelion natural rubbers were investigated using quick in situ simultaneous synchrotron time-resolved wide-angle X-ray diffraction/tensile measurements, for the first time. The SIC of sulfur crosslinked Hevea natural rubber was also evaluated for comparison. The SIC phenomena were clearly observed when guayule and dandelion natural rubbers were purified using acetone, then crosslinked with sulfur and subjected to strain. Guayule natural rubber showed a superior SIC upon high stretching to Hevea natural rubber, whereas dandelion natural rubber had a similar SIC to Hevea . The crosslinked guayule natural rubber had larger oriented amorphous components and larger crystallite sizes parallel to the stretching direction than the crosslinked dandelion and Hevea natural rubbers. These characteristic features resulted in larger crystallite volumes and lower orientation fluctuations of the crystallites in guayule natural rubber than in the others. It was speculated that the differences were because of their macromolecular structures and the amounts of non-rubber components in their matrixes. However, the SIC results clearly support the fact that both guayule and dandelion natural rubbers are the real alternatives to Hevea natural rubber.